Cyber Literacy for GIScience: Toward Formalizing Geospatial Computing Education. Issue 2 (3rd April 2019) - Shook, Eric; Bowlick, Forrest J.; Kemp, Karen K.; Ahlqvist, Ola; Carbajeles-Dale, Patricia; DiBiase, David; Kim, Eun-Kyeong; Lathrop, Scott; Ricker, Britta; Rickles, Patrick; Rush, Johnathan; Swift, Jennifer N.; et al.
Abstract : The unprecedented availability of geospatial data and technologies is driving innovation and discovery but not without the risk of losing focus on the geographic foundations of space and place in this vast "cyber sea" of data and technology. There is a pressing need to educate a new generation of scientists and citizens who understand how space and place matter in the real world and who understand and can keep pace with technological advancements in the computational world. We define cyberliteracy for GIScience (cyberGIScience literacy) and outline eight core areas that serve as a framework for establishing the essential abilities and foundational knowledge necessary to navigate and thrive in this new technologically rich world. The core areas are arranged to provide multiple dimensions of learning ranging from a technological focus to a problem solving focus or a focus on GIScience or computational science. We establish a competency matrix as a means of assessing and evaluating levels of cyberGIScience literacy across the eight core areas. We outline plans to catalyze the collaborative development and sharing of instructional materials to embed cyberGIScience literacy in the classroom and begin to realize a cyberliterate citizenry and academe. Key Words: big data, computational thinking, geographic education, GIS, spatial thinking.